We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
153
2
avatar

If f(x)=x^5-1/3, find f^-1(-31/96).

 Jul 31, 2018
 #1
avatar+21991 
+1

If f(x)=x^5-1/3, find f^-1(-31/96).

 

\(\begin{array}{|rcll|} \hline \boxed{f\left(f^{-1}\left(\dfrac{-31}{96}\right)\right) = \dfrac{-31}{96} \qquad (1) } \\\\ f(x) &=& x^5-\dfrac{1}{3} \quad | \quad x = f^{-1}\left(\dfrac{-31}{96}\right) \\\\ f\Big(f^{-1}\left(\dfrac{-31}{96}\right)\Big) &=& \left(f^{-1}\left(\dfrac{-31}{96}\right) \right)^5-\dfrac{1}{3} \\\\ && \left(f^{-1}\left(\dfrac{-31}{96}\right) \right)^5-\dfrac{1}{3} = \dfrac{-31}{96} \quad | \quad \text{ see } (1) \\\\ && \left(f^{-1}\left(\dfrac{-31}{96}\right) \right)^5 = \dfrac{1}{3} - \dfrac{31}{96} \\\\ && \left(f^{-1}\left(\dfrac{-31}{96}\right) \right)^5 = \dfrac{96-3\cdot 31}{3\cdot 96} \\\\ && \left(f^{-1}\left(\dfrac{-31}{96}\right) \right)^5 = \dfrac{3}{3\cdot 96} \\\\ && \left(f^{-1}\left(\dfrac{-31}{96}\right) \right)^5 = \dfrac{1}{96} \\\\ && f^{-1}\left(\dfrac{-31}{96}\right) = \sqrt[5]{\dfrac{1}{96}} \\\\ && f^{-1}\left(\dfrac{-31}{96}\right) = \sqrt[5]{0.01041666667} \\\\ && \mathbf{ f^{-1}\left(\dfrac{-31}{96}\right) = 0.40137078088 } \\ \hline \end{array}\)

 

laugh

 Jul 31, 2018
edited by heureka  Jul 31, 2018
 #2
avatar
0

Thank you so much! smiley

Guest Aug 1, 2018

24 Online Users

avatar